2019
DOI: 10.14203/j.baca.v40i2.476
|View full text |Cite
|
Sign up to set email alerts
|

Survei Penggunaan Media Sosial Di Kalangan Mahasiswa Kota Padang Menggunakan Teori Uses and Gratifications

Abstract: This research utilized theory uses and gratifications for discussing students' behavior in taking advantages of social media. Respondents came from 3 public universities in the city of Padang. The data collection method was done by distributing questionnaires and interviews, then, the data analyzed statistically. The results concluded that 97% of students claimed as social media active users. Based on the type of the application, the messenger/ chat app. was more preferable then the social networks. WhatsApp i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
53

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 11 publications
0
23
0
53
Order By: Relevance
“…WhatsApp appears to be the most popular and the most used social media (Saputra, 2019). Data collected from (Yustitia & Ashrianto, 2020) suggested that Indonesians have used social media such as WhatsApp as an access to information during the Covid-19 pandemic.…”
Section: Context (Facilities and Infrastructure)mentioning
confidence: 99%
See 1 more Smart Citation
“…WhatsApp appears to be the most popular and the most used social media (Saputra, 2019). Data collected from (Yustitia & Ashrianto, 2020) suggested that Indonesians have used social media such as WhatsApp as an access to information during the Covid-19 pandemic.…”
Section: Context (Facilities and Infrastructure)mentioning
confidence: 99%
“…It includes e-learning contents/materials, e-learning counseling/training, collaborative learning, and virtual classes (Ghirardini, 2011). It inspired by a study conducted by (Saputra, 2019), almost all students who used social media such as WhatsApp enabled social media-based learning as one of the e-learning media solutions during the pandemic. The concept of e-learning is distance learning that utilizes computer technology or commonly called the Internet (Horton, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…dan wawancara. Dari analisis yang dilakukan diperoleh informasi 97% mahasiswa mengaku sebagai pengguna aktif media sosial [1].…”
Section: Pendahuluanunclassified
“…IMT adalah nilai yang diambil dari perhitungan antara berat badan (BB) dan tinggi badan (TB) seseorang. Di Indonesia IMT diklasifikasikan menjadi underweight (< 18,5), normal (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)9), overweight (23-24,9), obesitas 1 (25-29,9), dan obesitas 2 (≥30). 3,4 Salah satu faktor yang berperan dalam menentukan status gizi seseorang adalah tingkat sosial ekonomi.…”
Section: Pendahuluanunclassified
“…Hal ini dikarenakan lelaki cenderung tidak memiliki ketertarikan dalam mengisi kuesioner. 10,11 Pada tabel 3 sebaran data Indeks Massa Tubuh, responden cenderung memiliki tubuh ideal Presentasi keluarga dengan status sosial ekonomi sedang pada penelitian ini lebih tinggi dibandingkan dengan data badan Pendidikan dan Pelatihan Keuangan (BPPK) tahun 2012. Peneliti beranggapan bahwa perbedaan ini diakibatkan oleh cara penilaian antara variabel yang berbeda dimana peneliti menggunakan kategori sosial ekonomi rendah, sedang, dan berat sedangkan BPPK menggunakan dua variabel yaitu menengah keatas dan menengah kebawah, juga pendapatan domestik bruto (pengeluaran perbulan) sebagai acuannya.…”
Section: Pembahasanunclassified